2020
DOI: 10.1111/jonm.13138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nurse staffing on patient‐safety outcomes: A cross‐sectional survey

Abstract: Patient safety is the most common topic in medical care (Flott et al., 2017; Lancet, 2016). Typical patient-safety outcomes in the field of nursing are falls, hospital-acquired infection (HAI), hospital-acquired pneumonia (HAP) and hospital-acquired pressure ulcer (HAPU). These outcomes challenge the quality of care. For example, falls have devastating physical, emotional and financial consequences (Godlock, Christiansen, & Feider, 2016). The hospital fall rate is almost 9 falls per 1,000 patient days, with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 31 publications
3
39
1
1
Order By: Relevance
“…The ratio of nurses who have worked for more than 10 years was inversely proportional to teamwork and nurses’ psychological problems (r s = 0.135, r s = 0.203), which indicated that nurses with more work experience had stronger abilities for team cooperation, communication skills, and coping skills under pressure. But research conducted by Wang et al [ 17 ] pointed out that the proportion of nurses with work experience of ≤5 years was a protective factor for preventing adverse events. Therefore, the proportion of nurses at all levels should be taken into account in the allocation of the nursing workforce in response to public health emergencies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of nurses who have worked for more than 10 years was inversely proportional to teamwork and nurses’ psychological problems (r s = 0.135, r s = 0.203), which indicated that nurses with more work experience had stronger abilities for team cooperation, communication skills, and coping skills under pressure. But research conducted by Wang et al [ 17 ] pointed out that the proportion of nurses with work experience of ≤5 years was a protective factor for preventing adverse events. Therefore, the proportion of nurses at all levels should be taken into account in the allocation of the nursing workforce in response to public health emergencies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that nurses may vary in their ability to cope with patients and in their working effectiveness depending on their length of experience, education levels and professional titles. Moreover, nurses with different professional–technical titles can be expected to play different roles in patient care, especially in China (Wang et al., 2020). Hence, the skill mix also matters to work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In acute care, multiple studies have demonstrated that better nurse staffing (ie, more care hours per client and day and more qualified care teams) is associated with better client outcomes. [10][11][12][13][14][15] For example, Driscroll et al 16 found in their meta-analysis that higher nurse staffing levels decreased the mortality risk by 14% (OR=0.86, 95% CI 0.79 to 0.94). Similarly, a systematic review by Kane et al 17 demonstrated that on intensive care units one registered nurse (RN) more per client day decreased the odds of hospital acquired pneumonia (OR=0.70; 95% CI 0.56 to 0.88), unplanned extubation (OR=0.49; 95% CI 0.36 to 0.67), respiratory failure (OR=0.40; 95% CI 0.27 to 0.59) and cardiac arrest (OR=0.72; 95% CI 0.62 to 0.84).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%